Biocoal - Quality control and assurance. (April 2020) - Pawlak-Kruczek, Halina; Arora, Amit; Gupta, Ashish; Saeed, Muhammad Azam; Niedzwiecki, Lukasz; Andrews, Gordon; Phylaktou, Herodotos; Gibbs, Bernard; Newlaczyl, Anna; Livesey, Penelope M.
Abstract: Torrefied biomass is said to have potential as a replacement for coal. One of the main goals of torrefaction is to make biomass resemble coal more in terms of its properties as a solid fuel. As a fuel, a novel fuel that is produced by thermal treatment of raw biomass, biocoal has to comply with the regulations of solid fuels from different regulatory bodies. The production regime is different in comparison to the thermally treated fuel already established on the market, such as charcoal. This might raise an issue with the bodies controlling the circulation of chemical substances in the market, such as ECHA in Europe. The aim of this paper is to recommend suitable analytical techniques in order to enable effective quality control. This is necessary if biomass of low and highly variable quality is supposed to become more uniform and turn into a commodity. Information given in many published studies seems sufficient to use of FTIR and NIR as quality control techniques. The use of NMR can be complementary but is limited due to the high cost of the analytical equipment and time-consuming sample preparation. Rapid testing techniques, such as FTIR ATR or NIR, might prove feasible for quality control of solid biofuels, such as biocoal, especially for in-house quality control purposes. This way proper quality assurance and compliance with various novel regulations, such as REACH, could be assured. Further research could be helpful, especially if results would be available in publicly available databases, such as Phyllis. Highlights: The need of wider use of novel, rapid analytical techniques is outlined. Novel analytical techniques, suitable for biocoal are described and compared. The literature on the analysis of biocoal, using techniques such as FTIR, NIR and NMR, is a subject of detailed review. Peaks, already determined in the literature, within the spectra of the aforementioned techniques, are listed in tables. Areas of future development and advantages of the novel techniques are assessed.